Investigação da amplificação do gene C-MYC no GIST de pacientes atendidos no HUJBB, no período de 1999 a 2009, em Belém-Pa - KATAOKA, Felipe Guilherme Hamoy (2023)
Gastrointestinal Stromal Tumors (GIST) is the most common stromal tumor of the gastrointestinal tract. Unlike other malignancies no associations that favor the onset of the disease are confirmed, even for know carcinogenic behaviors, such as tobacco smoke and alcohol. Diagnosis is determined by histological and immunohistochemical analysis and therapy depends on tumor resection’s possibility. For treatment of advanced disease, neo-adjuvant care, or adjuvant care imatinib mesylate is used. It’s a small molecule that inhibits tyrosine kinase with potent activity against transmembrane Kit receptors. Currently, in addition to tyrosine kinase inhibitors, anti-angiogenesis therapeutics are researched, however, those agents are still under clinical investigations. After surgery, the patient must be monitored by clinical, laboratorial and image exams in order to assess whether there was local recurrence or metastasis. The oncogene MYC (C - MYC) has been described as key element in several human carcinogenic processes and its amplification might be a predictor of aggressive and unfavorable outcome. Aims: to investigate the C – MYC amplification in histological slides of immunophenotypic diagnosed GIST patients of Hospital Universitário João de Barros Barreto, between January 1999 and October 2009. Methods: Epidemiological, analytical, descriptive and retrospective study, of secondary sources, done by data acquirement from patient files available at the DAME/HUJBB. Seven histological slides of GIST patients were made and subjected to Fluorescence In Situ Hybridization (FISH), according to the method described by Pinkel et al (2005) and modified by Calgano et al (2005). Results: there were no numerical aberrations, deletions and amplifications. Conclusions: the negative results for C – MYC amplification suggests that, perhaps, this is not the main mechanism involving C - MYC in GIST pathogenesis demanding, however, further researches with bigger samples to confirm this find, still with few positive results described in literature.